Cyber espionage: How the competition for intelligence challenges international law - Asbjørn Thranov (Danish Institute for International Studies (DIIS), 2023)
Cyber espionage has become a common method for states to gather confidential information in cyberspace. The vast interconnectedness of the Internet provides a target-rich environment for states to engage in low-risk collection of large amounts of data at an unprecedented speed and scale. Cyber espionage may look different from traditional espionage, but it is essentially an expression of the tension between competing states. States use espionage, cyber or otherwise, to strengthen their own position and security in competition with political, military, or economic rivals. In this manner, cyber espionage is best understood as an integral part of an ongoing intelligence contest in cyberspace. This report explores how international law applies to peacetime cyber espionage. By taking stock of recent legal statements by states, this report specifically examines how states have interpreted the principles of territorial sovereignty and non-intervention in the cyber context. The report also analyses the legal implications of provision of intelligence and cyber support to Ukraine by Western states.
Keywords: 300; cyberspace; espionage; international law; national sovereignty; Ukraine; Western states